Surgical Treatment of Endo-periodontal Lesion – A Case Report - Shopova, Dobromira (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Periapical lesions are a pаthological changes that occur in most of poorly endodontically treated teeth. Endodontic and periodontal diseases are caused by a mixed anaerobic infection. Periodontal disease produces lesions in the tooth-supporting tissues. Generalized periodontitis comprises hard and soft tissue at the whole dentition. Surgical methods of treatment include etiological and pathogenetic methods – removal of pathological tissue, destruction of the bacterial causative agent, and recovery of lost tissue. Recognition and management of risk factors (local and general) increase the chances of a successful treatment outcome. The combined surgical protocol presented in this article is the last step before extraction. Especially in the frontal area, dentist should try to keep the esthetics, maintaining the tooth and the surrounding bone. CASE REPORT: The presented patient is a 59-year-old lady with generalized periodontal disease and periodontitis apicalis chronica dentis 21. Bone graft covered by soft-tissue graft was used to fill the defects around the apex and surrounding the teeth. After 5 months, the apical lesion was in very good condition according to radiological and clinical examination. The periodontal lesion was almost at the same vertical condition as the initial situation, but this surgery method aims to make bone thicker for support of the mucosa. The risk factors were smoking, average level of oral hygiene, and osteoporosis. CONCLUSION: The combination of different clinical protocols is a necessity in surgical practice. Knowledge of the etiology and pathogenesis of the disease allows the application of adequate methods of treatment. The result was satisfactory.